Optimists die first - Nielsen-Fernlund, Susin, 1964- (New York : Wendy Lamb Books, 2017)
"When Petula de Wilde, who is anything but wild, meets Jacob in their school's dorky art therapy program, his friendship (and something more) helps her overcome intense fears since her sister died. And he has a secret of his own"--
Keywords: Fear -- Fiction; Emotional problems -- Fiction; Friendship -- Fiction; Love -- Fiction